2017
DOI: 10.4097/kjae.2017.70.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic interfascial nerve block for breast surgery in a pregnant woman: a case report

Abstract: Regional anesthesia for non-obstetric surgery in parturients is a method to decrease patient and fetal risk during general anesthesia. Thoracic interfascial nerve block can be used as an analgesic technique for surgical procedures of the thorax. The Pecs II block is an interfascial block that targets not only the medial and lateral pectoral nerves, but also the lateral cutaneous branch of the intercostal nerve. Pecto-intercostal fascial block (PIFB) targets the anterior cutaneous branch of the intercostal nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…Table 2 summarises the articles included, technique of fascial plane block used and the main outcome related to it. [ 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 summarises the articles included, technique of fascial plane block used and the main outcome related to it. [ 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 ]…”
Section: Resultsmentioning
confidence: 99%
“…Interfascial plane blocks described for analgesia of chest have been found to be covering these dermatomes and thus appear to be effective for perioperative analgesia following breast surgeries [ Table 1 ]. [ 8 9 10 11 12 13 14 ] Since the description of these newer and safer interfascial plane blocks, various authors have studied their use in breast surgeries. At present, it is difficult to determine the superiority of one technique over the other in view of insufficient data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al have reported Pecs II block and internal intercostal plane block without general anesthesia for a huge breast fibroadenoma resection in a patient with fear for general anesthesia [13]. Hong et al have reported modified Pecs II block (below the serratus muscle as the second injection) and pectointercostal fascial block without general anesthesia for partial resection of recurrent breast cancer in a parturient [14]. Compared with these reports, our case was challenging in terms of determining the dose of local anesthetics because the body weight of the patient was only 30 kg.…”
Section: Discussionmentioning
confidence: 99%